The Concept of Ifta 'in Establishing Halal Law (Study of Usul fiqh on Legal Determination Methods) - Muchammad Fauzi; Amalia Nur Azizah; Lena Nurfauziyah (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2019)
Fatwa and qadla activities as a form of delivering the laws of God, are the great mandate. In addition to requiring intellectual expertise, the fatwa giver must have moral virtue and spiritual intelligence. Indeed, this should be the figure of a scientist, especially the scholars who pursue Shari'a scientific fields. They must be able to create a balance between the power of reason and intuition of dhikr. Plus the level of concern for the social environment of the community. Because in their hands the change agenda is carried out.